Selected immunoendocrine measures for monitoring responses to training and match load in professional association football: a review of the evidence - Springham, M.; Newton, R. U.; Strudwick, A. J.; Waldron, M. (International Journal of Sports Physiology and Performance, 2022)
Biomarkers relating to player "stress balance," immunological (ie, immunoglobulin-A), and hormonal (ie, testosterone and cortisol [T:C]) status are now commonly used in football. This article is our critical review of the scientific literature relating to the response of these measures to player load and their relationships with player health. The commonly reported relationship between immunoglobulin-A and training or match load highlights its sensitivity to changes in psychophysiological stress and the increased risk of compromised mucosal immunity. This is supported by its close relationship with symptoms of upper respiratory tract infection and its association with perceived fatigue in football players. Testosterone and cortisol concentrations and the testosterone-cortisol ratio are sensitive to changes in player load, but the direction of their response is often inconsistent and is likely influenced by player training status and non-sport-related stressors. Some evidence indicates that sustained periods of high training volume can increase resting testosterone and that sustained periods of low and high training intensity can increase resting cortisol, compromising the testosterone-cortisol ratio. These findings are noteworthy, as recent findings indicate interrelationships between testosterone, cortisol, and testosterone:cortisol and perceived measures of fatigue, sleep quality, and muscle soreness in football players. Variability in individual responses suggests the need for a multivariate and individualized approach to player monitoring. Overall, we consider that there is sufficient evidence to support the use of salivary immunoglobulin-A, testosterone, cortisol, and testosterone:cortisol measures as part of a multivariate, individualized player monitoring system in professional football.